Prevalence of breakfast skipping among children and adolescents: a cross-sectional population level study - Alanna Sincovich; Hero Moller; Lisa Smithers; Mary Brushe; Zohra S. Lassi; Sally A. Brinkman; Tess Gregory (BMC, 2022)
Abstract Background Interventions to promote breakfast consumption are a popular strategy to address early life inequalities. It is important to understand the epidemiology of children and adolescents who skip breakfast so that interventions and policy can be appropriately considered. This study investigated the prevalence of breakfast skipping among a contemporary, population-wide sample of children and adolescents in Australia. Methods Participants were grade 4-12 students (n = 71,390, 8-18 years) in South Australian government (public) schools who took part in the 2019 Wellbeing and Engagement Collection. The prevalence of breakfast skipping (never, sometimes, often, or always) was calculated for the overall sample and stratified by gender, school grade, socioeconomic status and geographical remoteness. Multinomial logistic regression analyses were conducted to determine the relative risk ratio of sometimes, often, and always skippers compared with never skippers, according to demographic characteristics. Results Overall, 55.0% of students reported never skipping breakfast, 17.4% reported sometimes skipping, 18.0% reported often skipping, and 9.5% reported always skipping breakfast. Skipping breakfast was more prevalent among females, students in senior grades, and those living in socioeconomically disadvantaged and regional and remote areas. Analyses disaggregated by gender revealed that grade level gradients in breakfast skipping were more marked among females compared to males. Conclusions Breakfast skipping among children and adolescents appears considerably more prevalent than previous research suggests. Drivers of breakfast skipping across population sub-groups need to be explored to better inform strategies to promote breakfast consumption.